A review of safe‐staffing models and their applicability to care homes. (26th December 2016) - Mitchell, Gary; Cousins, Carol; Burrows, Ruth; Cousins, Gary
Abstract : Presently, there are a range of evidence‐based staffing tools that have been used to inform nursing, midwifery and health care capacity. These tools are designed to be used with professional judgement and include frameworks such as Rhys Hearn, the National Services Scotland Care Home Staffing Project, a variety of Royal College of Nursing Tool Kits including the Older People in Hospital's tool and the only National Institute of Clinical Excellence approved safe‐staffing tool, Shelford's Safer Nursing Tool. These safe‐staffing tools are used to score a patient's or resident's level of dependency across a number of domains, for example a patient/resident's ability to wash, dress, mobilise or fulfil their own elimination needs. While these tools have been beneficial with regards to informing staff levels there are a number of limitations that are important to highlight. Succinctly, most are not readily applicable to care home settings nor do they focus on more person‐centred aspects of care.